2014
DOI: 10.3103/s1063457614010055
|View full text |Cite
|
Sign up to set email alerts
|

Superhard coatings of the (Zr-Ti-Si)N and (Ti-Hf-Si)N systems produced by vacuum-arc deposition from a separated flow

Abstract: Abstract-Multicomponent hard coatings based on nitrides of Si doped transition metals have been pro duced by vacuum-arc deposition with the use of a RF generator and separation of an ion-plasma flux. Physico mechanical and tribotechnical characteristics of coatings have been studied. The possibility of their use as efficient protective coatings has been shown. DOI: 10.3103/S1063457614010055Keywords: protective coatings, vacuum-arc deposition, nitrides of metals, cutting tools. INTRODUCTIONOne of the priority d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Figure 6(b) shows the behaviour of the variation in mass during 300 cycles for the Ti6Al4V alloy. As shown in the graph, the generation of oxide layers was constant, which is associated with the movement of metal cations during the stage of oxide growth towards the outside, which generates voids that separate the oxide layer and the Ti6Al4V substrate [2325]. It can be seen that the change in mass becomes greater as the number of thermal corrosion cycles increases, which indicates that the oxide layer has a certain protective behaviour [21,26].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6(b) shows the behaviour of the variation in mass during 300 cycles for the Ti6Al4V alloy. As shown in the graph, the generation of oxide layers was constant, which is associated with the movement of metal cations during the stage of oxide growth towards the outside, which generates voids that separate the oxide layer and the Ti6Al4V substrate [2325]. It can be seen that the change in mass becomes greater as the number of thermal corrosion cycles increases, which indicates that the oxide layer has a certain protective behaviour [21,26].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the data of X-ray diffraction studies [6][7][8] indicates the characteristic structural features of coatings formed from targets of identical composition. The properties of the coatings differ greatly depending on the separation application, pressure of the reaction gas and magnitude of the displacement potential.…”
Section: Analysis Of Research Resultsmentioning
confidence: 99%
“…Fragments of X-ray photographs illustrate the determination of the crystal lattice deformation of the (Ti-Hf-Si)N coating with separation by superimposing lines under oblique shooting conditions: for the sample (U  -100 V) a deformation of -1.9 % is observed (the lattice parameter a  0.4305 nm), and -1.6 % for the sample (bias potential of -200 V, a  0.4303 nm) [6][7][8]. Fig.…”
Section: Analysis Of Research Resultsmentioning
confidence: 99%
“…In the greatest degree this refers to coatings produced at the lowest working pressure p N = 6.0 × 10 -4 Torr (Fig. 1), at which because of a lower density of a gaseous medium and, accordingly, long length of the particles free path, the mean loss of the energy of particles vaporized from a cathode at their movement from the vaporizing cathode to the substrate is the lowest [22]. The analysis of the elemental composition showed that after a high temperature annealing the relative contents of the coating metal components did not practically change.…”
Section: Resultsmentioning
confidence: 99%